2005
DOI: 10.18084/1084-7219.11.sp1.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a Hartford Gero-Rich Project on a Bachelor of Social Work Program

Abstract: In response to the greater need for professionally educated Bachelor of Social Work social workers to work with older adults, a multipronged approach was developed and implemented to infuse gerontology content into the undergraduate social work curriculum at a large state university in Texas. Efforts were made to help ensure that curricular and organizational changes would be sustained for the long term. These initiatives were funded by and were part of the national Hartford Geriatric Enrichment in Social Work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, Kane (1999) found that knowledge of Alzheimer's disease was significantly correlated with willingness to work with older adults with the disease. However, Paton et al (2001) found that knowledge of aging was not associated with student interest in working with older adults; thus, it remains unclear how knowledge of aging relates to student career interests (Barton, Cohen, Thomas, & Sandel, 2005).…”
Section: Student Knowledge About Working With Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kane (1999) found that knowledge of Alzheimer's disease was significantly correlated with willingness to work with older adults with the disease. However, Paton et al (2001) found that knowledge of aging was not associated with student interest in working with older adults; thus, it remains unclear how knowledge of aging relates to student career interests (Barton, Cohen, Thomas, & Sandel, 2005).…”
Section: Student Knowledge About Working With Older Adultsmentioning
confidence: 99%
“…Coursework taken in a variety of different disciplines has proven beneficial in increasing aging knowledge among college students; Barton et al (2005) have provided an excellent review of this literature. For the social work students who participated in her study, Olson (2002) found that a time-limited educational module proved to be a promising intervention for increasing knowledge about assessment and intervention with older adults for her social work undergraduate and graduate students; however, their interest in working with elders did not change, except for a slight decline in the Master of Social Work (MSW) group.…”
Section: Student Knowledge About Working With Older Adultsmentioning
confidence: 99%